Optimizing oil spill cleanup efforts: A tactical approach and evaluation framework. Issue 1 (15th December 2017) - Grubesic, Tony H.; Wei, Ran; Nelson, Jake
Abstract: Although anthropogenic oil spills vary in size, duration and severity, their broad impacts on complex social, economic and ecological systems can be significant. Questions pertaining to the operational challenges associated with the tactical allocation of human resources, cleanup equipment and supplies to areas impacted by a large spill are particularly salient when developing mitigation strategies for extreme oiling events. The purpose of this paper is to illustrate the application of advanced oil spill modeling techniques in combination with a developed mathematical model to spatially optimize the allocation of response crews and equipment for cleaning up an offshore oil spill. The results suggest that the detailed simulations and optimization model are a good first step in allowing both communities and emergency responders to proactively plan for extreme oiling events and develop response strategies that minimize the impacts of spills. Highlights: A spatial optimization model is built for tactical oil spill response efforts. The developed framework is spatially and temporally explicit. We analyze three oil spill scenarios to test the response model. The results enhance geospatial intelligence for scenario planning and response.